UFMylation inhibits the proinflammatory capacity of interferon-γ–activated macrophages - Balce, Dale R. (Proc Natl Acad Sci U S A, 2021)
Macrophages activated with interferon-γ (IFN-γ) in combination with other proinflammatory stimuli, such as lipopolysaccharide or tumor necrosis factor-α (TNF-α), respond with transcriptional and cellular changes that enhance clearance of intracellular pathogens at the risk of damaging tissues. IFN-γ effects must therefore be carefully balanced with inhibitory mechanisms to prevent immunopathology. We performed a genome-wide CRISPR knockout screen in a macrophage cell line to identify negative regulators of IFN-γ responses. We discovered an unexpected role of the ubiquitin-fold modifier (Ufm1) conjugation system (herein UFMylation) in inhibiting responses to IFN-γ and lipopolysaccharide. Enhanced IFN-γ activation in UFMylation-deficient cells resulted in increased transcriptional responses to IFN-γ in a manner dependent on endoplasmic reticulum stress responses involving Ern1 and Xbp1. Furthermore, UFMylation in myeloid cells is required for resistance to influenza infection in mice, indicating that this pathway modulates in vivo responses to infection. These findings provide a genetic roadmap for the regulation of responses to a key mediator of cellular immunity and identify a molecular link between the UFMylation pathway and immune responses.